FeNO-based asthma management results in faster improvement of airway hyperresponsiveness. Issue 4 (3rd October 2018) - Bernholm, Katrine Feldballe; Homøe, Anne-Sophie; Meteran, Howraman; Jensen, Camilla Bjørn; Porsbjerg, Celeste; Backer, Vibeke
Asthma is characterised by inflammation and respiratory symptoms. Current asthma treatment is based on severity of asthma symptoms only. Exhaled nitric oxide fraction ( F eNO ) is not recommended by the Global Initiative for Asthma guidelines. The aim was to compare the usefulness of a F eNO guided versus symptom-based treatment in achieving improved asthma control assessed by airway hyperresponsiveness (AHR). 80 asthmatic patients were included in a double-blinded, parallel, randomised controlled trial with follow-up visits after 8, 24 and 36 weeks. Treatment was tailored using either a F eNO or Asthma Control Questionnaire (ACQ) based algorithm. Inclusion criteria were asthma symptoms and a provocative dose causing a 15% fall in forced expiratory volume in 1 s <635 mg mannitol. At each visit AHR, F eNO, ACQ and blood tests were performed. No differences between the two groups were found at inclusion. AHR from 8 to 24 weeks was improved in the F eNO group compared to the ACQ group (response dose ratio (RDR) geometric mean (95% CI): 0.02 (0.01–0.04) versus 0.05 (0.03–0.07), respectively, p=0.015). AHR to mannitol at 36 weeks showed no differences between the two groups (mean difference RDR (95% CI): −0.02 (−0.05–0.02), p=0.3). Total doses of inhaled steroid and number of exacerbations were similar (p>0.05). When using F eNO as a treatment management tool, lowering of airway responsiveness occurred earlier than using ACQ. However, airway responsiveness and asthma control after 9 months were similar. Asthma management using F eNO provides faster asthma control but is similar to symptom-based management after 9 months http://ow.ly/DGNf30lqGJm